Synergistic effect of recycled E-waste fiber and polyvinyl alcohol on the properties of green concrete incorporating recycled concrete aggregate - Burachat Chatveera; Ali Ejaz; Muhammad Adnan Hanif; Panumas Saingam; Qudeer Hussain; Chatpan Chintanapakdee; Tosporn Arreeras; Gritsada Sua-iam (Developments in the Built Environment)
The growing demand for sustainable construction highlights the need for innovative concrete solutions using waste materials. Although recycled concrete aggregate (RCA), polyvinyl alcohol (PVA), and recycled electronic waste fibers (E-waste fibers) have been studied individually, their combined effects remain underexplored. This study addresses this gap by investigating the synergistic effects of coarse RCA (CRCA) and E-waste fibers on the fresh, mechanical, durability, thermal, and economic properties of green concrete. Fly ash replaced 20 % of cement, and PVA was added at 1 % by cement weight. Results showed that increasing CRCA content reduced workability and strength due to porosity. However, incorporating 4.5 % E-waste fibers significantly improved mechanical performance by bridging microcracks. Higher fiber contents negatively affected durability and workability. Thermal conductivity decreased with more CRCA and fibers, enhancing insulation. Economic analysis confirmed that 4.5 % E-waste fiber offers cost-effective performance. This study supports the sustainable use of electronic and construction waste in concrete.